Budaya Sekolah Pada Sekolah Menengah Pertama di Indonesia - Mustari, Mohammad (Program Studi Magister Pedagogi, 2013)
Mohammad MustariDirektorat Pendidikan Dasar Kemendikbud Indonesia Email: m_mustary@yahoo.co.idAbstract:This study aimed at investigating the level of school cultures at Junior High Schools in Indonesia. This study engaged 218 principals in Java, Sumatra, Kalimantan, Bali, Nusatenggara, Sulawesi, and Papua. This study employed correlational descriptive-quantitative method and used Liker Scale with 5 choices to measure the aspects of the principals’ leadership and school culture variables. The data were analyzed using SPSS program version 16, based on the mean and standard deviation. The findings revealed that the school culture was high for the whole aspects such as collaboration, school vision, school comprehensive planning, transformational leadership, professional values, teachers as learners, spirit of solidarity, school empowerment, and schools values.Key words: school cultures, collaboration, school valuesAbstrak:Penelitian ini dilaksanakan untuk mengukur tingkat budaya sekolah pada Sekolah Menengah Pertama di Indonesia. Penelitian ini melibatkan 218 orang kepala sekolah yang berdomisili di Pulau Jawa, Sumatra, Kalimantan, Bali, Nusatenggara, Sulawesi dan Papua. Kajian ini berbentuk tinjauan deskriptif-kuantitatif korelasional menggunakan angket skala Likert dengan 5 pilihan untuk mengukur aspek-aspek variabel kepemimpinan kepala sekolah dan budaya sekolah. Data diolah menggunakan program SPSS versi 16, menggunakan rata-rata dan standar deviasi. Hasil penelitian menunjukkan tingkat budaya sekolah tinggi untuk keseluruahan aspek meliputi: kolaborasi; visi bersama; perencaan komprehensif sekolah; kepemimpinan transformasional; nilai professional; guru sebagai peserta didik; semangat setia kawan; pemberdayaan bersama; dan nilai-nilai sekolah.Kata kunci: budaya sekolah, kolaborasi, nilai-nilai sekolah